INTERACTIVE DIDACTIC SEQUENCES: DISCUSSING THE CONCEPT OF BISECTOR OF AN INTERNAL ANGLE OF ANY TRIANGLE (Interdisciplinary Studies Journal, 2025)
he study proposes the development of the concept of the bisector of an internal angle of any triangle by a group of eighth-grade students in a school located in the Semi-Arid region of Potiguar, using the Interactive Didactic Sequence (ITS) as a pedagogical approach. The responses derived from the students' preexisting knowledge were reviewed and condensed into sets to derive a definition to be debated, using the GeoGebra Learning Object as a teaching resource. GeoGebra proved to be an interactive software that facilitates learning. Regarding the concept under study, the presented conceptual maps demonstrated that the students improved their knowledge in a conversational and interactive manner. The conclusions reveal that the IDS approach fosters interactive discussions, enabling the construction of knowledge based on the students' prior understanding.
Keywords: IDS; GeoGebra Learning Object; Concept Map; Teaching